Application of an assisting model to improve care in ambulatory major surgery and short stay - Javier Cruz Rodríguez; Abraham Dimas Reyes Pérez; Joaquín Zurbano Fernández; María del Carmen Rodríguez Fernández; Fara Rodríguez Becerra; Eusebio Alejandro Hernández Lema (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: Difficulties have been evidenced in the coordination between primary and secondary health levels in the process of patient care in ambulatory major surgery and short stay surgery. Objective: to evaluate the satisfaction and quality perceived by patients and family members with the application of an assisting model, a procedure guide and a clinical history model for care improvement in ambulatory major surgery and short stay surgery. Methods: a quasi-experimental study was conducted to evaluate the satisfaction and perceived quality of patients with their experience in ambulatory or short-stay elective major surgery, and by their relatives. The experimental group was constituted of 22 patients and 22 relatives, and the control group was composed of 28 patients and 28 relatives. Satisfaction was assessed using a Likert scale. The Mann-Whitney U-score was applied for comparisons between the experimental and control groups and for two independent samples. Results: there was correspondence between both groups of patients, experimental and control, with a similar behavior between satisfaction and indicators of perceived quality. In the patients of the experimental group, satisfaction and perceived quality indicators showed better results in the post-test, with the exception of the indicator accessibility. Conclusion: the application of assisting proposals contributed to the achievement of high levels of satisfaction and perceived quality in patients and relatives.